The Effectiveness of mobile learning media using Smart Apps Creator on Economic subjects - Aristia, Atikah; Kartikowati, Sri; Natuna, Daeng Ayub (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
This study aims to produce mobile learning media using the Smart Apps Creator and to determine the effectiveness of these media in increasing student interest in learning. The 4D model (Define, Design, Develop, and Disseminate) is used in the research and development process for this project. This research is limited to the development phase. The participants in this research were XI IPS SMA PGRI Pekanbaru students. Data was obtained based on interviews and questionnaires. Based on the substantiation of media and content specialists, the research findings indicate that the use of mobile learning media created by smart apps creator is feasible, with 87% of the categories being very appropriate according to media experts and 83% of the categories being very appropriate based on subject matter experts. Paired sample t-test obtained differences and positive increases in student learning interest before and after using smart apps creator-based mobile learning media, so the media is said to be effective. The use of media received a good response from students; 64.5% consider mobile learning media using smart app creators to be very practical and helpful in learning, while the remaining 35.5% consider it practical. This research is limited to APBN and APBD material and is only carried out until the development stage.